Perspectivas comunicacional e hipertextual à luz das tecnologias em educação em meio ao uso de Fóruns e Chats na Didática da Matemática - NASCIMENTO, Weldson Luiz (2009)
This work is the result of a qualitative research on participative nature that arouse from the study of facts and analysis of bachelor in mathematics II (DID2), during the first semester of 2008 in the college of mathematics and statistics at Goiás Federal University (UFG). The main purpose of this research was to verify the range on which the virtual classes could either or neither contribute to the learning process. The study was shaped according to 50% of presence classes and 50% of non presence ones. Virtual learning was used for non presence activities (AVA) Moodle. In the context of the research, the researcher was a copartner in the working up and effective accomplishment of pedagogical activities and virtual ones (AVA), as well as a researcher in exercise in the presence and non presence activities, developed by his/her professor. Because of the pedagogical range that the subject presented itself, thematic cuttings were essential for data analysis. Communicational perspectives were researched then, hyper textual information about the developed subject and the above-mentioned (AVA). With the analysis categories of every perspective above-mentioned, interchanges of speech were developed in forum and chats when, they were contrasted it was found the construction of an interactive communication and expressive textual dialogue as the priority perspective signalized. Simultaneously, the dissertation also contributed to sections, whose debates gave a subsidy to themes, not totally clarified by the approach pertaining to a not present education (EaD). The themes approached passed by possible differences between interaction and interactivities, and also about the possibility to create communicational spaces, which developed themselves. It also holds conceptions about emblematical themes, technologies of information and communication (TIC) and (AVA). The legal base about the EaD and some contributions examined in the development of the subject that lay the foundation and stimulate virtual practices. In this context the research created new thoughts about pedagogical virtual practices, mainly to involve the researched subject, a non conventional practice in similar research in the field of Mathematics. This practice approaches a subject in the field of education not for the specific Mathematics subject.Perspective and hypertextual communication in the light of technology in education through the use of Forums and Chat the Didactics of Mathematics